Trade‐off design of positive‐feedback based islanding detection. (21st October 2020) - Zheng, Chengyan; Sun, Yao; Guo, Bin; Jiang, Taowen; Feng, Wendong; Zhang, Xin; Guerrero, Josep M.
Abstract: Background: Positive feedback (PFB) based anti‐islanding schemes have gained wide popularity in islanding detection. However, the disturbance injected by the PFB methods can easily cause the destabilization of the grid‐connected distributed generation (DG) system. Therefore, how to effectively balance the normal operation of the grid‐connected system and the effectiveness of the islanding detection is essential. Purpose: In this study, the trade‐off design of the PFB control gain is given, where the requirements of grid‐tied control and islanding detection are simultaneously considered. Design/Method: Firstly, the small‐signal models are established to investigate the stability of a DG system in both islanded and grid‐connected mode. Meanwhile, the minimum and maximum PFB gains are obtained by root loci method, thus, the PFB gain can be accurately determined without trial and error. Additionally, the Sensitivity analysis is conducted for the DG system. Factors such as grid impedance, phase‐locked loop (PLL) bandwidth, proportional‐integral (PI) controller gains, inverter output current rating, and load quality factor are thoroughly taken in account, which provides the guideline of the PFB gain design. Finally, simulations and experiment tests are performed to confirm the theoretical analysis. Results: This paper presents a trade‐off design of the PFB control gain for a DG system from the essence of the PFB algorithm. The essence of PFB as well as the cause of the interconnected system instability are revealed. In addition, the minimum and maximum PFB gains are obtained by the stability analysis. Conclusions: A high PFB gain will contribute to the islanding detection but deteriorate the grid‐connected system stability. Further, it is found that 1) the maximum PFB gain decreases with the grid impedance increasing, 2) the increase in PLL bandwidth and the integral gain in current loop lead to a decrease in the maximum PFB gain, 3) the minimum PFB gain which reflects the islanding detection capability of the VPF scheme is not affected by the load quality factor, 4) when the inverter output current is large, a reasonable PFB gain may not be found as the islanding detection and the normal operation of the grid‐connected system cannot be balanced. Abstract : Schematic diagram of a three‐phase inverter‐based DG system with PFB control